O processo de simbiose entre Dom Quixote e Sancho Pança sob a ótica crítica da linguística sistêmico-funcional - Santos, Vanessa Alves Maximo dos (2017)
Quixote, by Miguel de Cervantes Saavedra, whose first part came to light in 1605, is one of the best known works in world literature and has received several interpretations. A controversial subject concerns the proposal of Salvador de Madariaga y Rojo, who proposed a slow and persistent process of symbiosis between the characters Don Quixote and Sancho Panza, from the work Quixote by Miguel de Cervantes Saavedra, resulting in the sanchificación of dom Quixote and in Sancho's quixotization. The proposal, made in the first half of the twentieth century, caused great repercussion in the scope of the Cervantine studies. The present work seeks to analyze the speech and the behavior of the characters throughout the narrative, in order to confirm or not Madariaga's proposal and, for that, concentrates on the analysis of two chapters "Moinhos de Vento" (Chapter VIII) and "Cravilenho" (cap.XLI) that make up the first and second part of Quixote, respectively. The research, which is a critical one, has the basic support in the theoretical-methodological proposal of Systemic-Functional Linguistics (LSF), in which the interpersonal metafunction encompasses the notion of modality as welll as the notion of appraisal – subdivided in affection (emotions), judgement (ethic) and appreciation (aesthetics). SFL allows the relation of the lexical-grammatical choices of the microstructure of the text with the macrostructure of the power relations and discourse ideology. The research should answer the following questions: (a) What grammatical choices confirm the sanchification of Don Quixote and the quixotization of Sancho? (b) What role does appraisal play in this process? (c) How is social critique made in this context? The analysis proves that there is in fact a change in the character of both characters, in terms of a mutual influence that happens throughout the narrative, in which a more careful examination discloses the implicit social critique woven by Cervantes